Simultaneous Spectrophotometric Determination of Levofloxacin and Ornidazole from Combined Dosage Form - CHEPURWAR, S.B.; SHIRKHEDKAR, A.A.; BARI, S.B.; SURANA, S.J. (Asian Journal of Chemistry, 2010)
A simple, rapid, accurate and precise spectrophotometric method has been developed for simultaneous estimation of levofloxacin and ornidazole from tablet dosage form. Proposed method involves formation of simultaneous equations at 289 and 320 nm, using distilled water as a solvent. The linearity was observed in the concentration range of 4-20 μg/mL for levofloxacin and 4-20 μg/mL for ornidazole. The results of analysis have been validated statistically and by recovery studies.